(untitled) (Academic Journal of Internal Affairs, 2020)
Tibor Király, a determinative personality in education and research of criminal procedural law for seven decades, celebrated his 100th birthday on 11. July 2020. This long and comprehensive life is not only unique because nobody else from Hungarian criminal lawyers has lived one century, but also because Professor Király has received, rightful, practically each form of professional recognitions. His work and professional attendance is multiple and diversified. He created a new school as legal scholar who helped for several generations to develop a way of thinking and a legal mentality based on humanism. A progressive thinking researcher, who has always been – beside appreciating traditions - more longsighted as his age. In his works – proceeding from scientific historical drafting – he adumbrated a picture of the future, a picture of a legal system ready for renewal. An academic, an organizer of science - who plays an important role also in forming of the community of scholars - showing the way not only for the future generation but also for fellow scholars in Hungary and abroad. A Hungarian legal scholar from the Hungarian uplands, who has done a lot in the frame of the „Bethlen Gábor Foundation” for preserving and enrichment of values of the Hungarians and simultaneously for a peaceful coexistence of the nations in Central-Europe. His life and work can be exemplary for all lawyers.